Game Learning to Optimize Learning in Disaster Area - Kusumandari, Raﬁka Bayu; Wibawa, Basuki; Muchtar, Hartati (KnE Social Sciences, 2019)
In terms of earth science, Indonesia is a very interesting area. But Indonesia is also the mostaffectedcountry.OneofthebiggestnaturaldisastersthatstruckIndonesiaregion is the 2004 Aceh Tsunami. This condition causes the destruction of various facilities including infrastructure in the world of education so that often hampers the learning process. Though education is a very valuable investment in human life. Therefore, various developments continue to be made to create various learning alternatives in supporting the education process. The use of technology will help the implementation of the learning process although facilities and infrastructure are minimal. One of the technologies used is the use of smartphones for learning. By using Android-based learning game is expected to be an alternative model of education that is effective, interesting, interactive and fun. Utilization of this android based learning game in addition to optimizing learning can also reduce trauma (trauma healing) in children after the disaster. Keywords: Android-based Learning Game, Trauma, Optimizing Learning, Disaster